2020
DOI: 10.1111/jfbc.13525
|View full text |Cite
|
Sign up to set email alerts
|

Role of potato protein hydrolysate and exercise in preventing high‐fat diet‐induced hepatocyte apoptosis in senescence‐accelerated mouse

Abstract: Nonalcoholic fatty liver disease (NAFLD) is considered to be a serious clinical complication, which could cause significant liver dysfunction including fibrosis, cirrhosis, and cancer. Obesity could lead to NAFLD and contributes to liver disorder and related complicated liver diseases. Effect of exercise combined with alcalase treatment derived potato protein hydrolysate (APPH) on high-fat diet (HFD)-induced hepatic injury was investigated in senescence accelerated mouse-prone 8 (SAMP8) mice in the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…PP902 refers to a potato protein that undergoes hydrolysis with alcalase for a duration of 2 h. It contains 9% of 200 ppm hydrolysates and exhibits lipolysis‐stimulating characteristics, offering potential bioactivities 26 . Our research findings revealed that potato protein hydrolysate (PPH) exhibits a range of bioactivities, encompassing antioxidative, antidiabetic, anti‐sarcopenia, anti‐aging, hepatoprotective, cardioprotective, and renal protective effects 25,26,32–34 . In one of our recent studies, we demonstrated that a decapeptide derived from potato hydrolysate has the capacity to promote myogenic differentiation and alleviate the detrimental effects of high glucose‐associated alteration in protein synthesis and mitochondrial biogenesis in myoblasts 25 …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…PP902 refers to a potato protein that undergoes hydrolysis with alcalase for a duration of 2 h. It contains 9% of 200 ppm hydrolysates and exhibits lipolysis‐stimulating characteristics, offering potential bioactivities 26 . Our research findings revealed that potato protein hydrolysate (PPH) exhibits a range of bioactivities, encompassing antioxidative, antidiabetic, anti‐sarcopenia, anti‐aging, hepatoprotective, cardioprotective, and renal protective effects 25,26,32–34 . In one of our recent studies, we demonstrated that a decapeptide derived from potato hydrolysate has the capacity to promote myogenic differentiation and alleviate the detrimental effects of high glucose‐associated alteration in protein synthesis and mitochondrial biogenesis in myoblasts 25 …”
Section: Discussionmentioning
confidence: 87%
“…26 Our research findings revealed that potato protein hydrolysate (PPH) exhibits a range of bioactivities, encompassing antioxidative, antidiabetic, anti-sarcopenia, anti-aging, hepatoprotective, cardioprotective, and renal protective effects. 25,26,[32][33][34] In one of our recent studies, we demonstrated that a decapeptide derived from potato hydrolysate has the capacity to promote myogenic differentiation and alleviate the detrimental effects of high glucose-associated alteration in protein synthesis and mitochondrial biogenesis in myoblasts. 25 Extensive evidence has established that inflammation constitutes a significant contributing factor to the development of osteoporosis and other bone-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatically released peptides may display better functional properties than their parent protein molecules and consequently exhibit higher activity in food systems (Kamnerdpetch, Weiss, Kasper, & Scheper, 2007;Moreno et al, 1993). Moreover, potato protein hydrolysates have also been shown to have beneficial health effects in vivo (Chuang et al, 2020), illustrating their potential as both a functional and bioactive ingredients. Amphiphilic surfactants are widely used as emulsifiers as they contain both hydrophobic and hydrophilic regions, which are capable of reorganising at the oil-water interface and thereby stabilize the emulsion by decreasing the interfacial tension between the two immiscible liquids (McClements & Jafari, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatically released peptides may display better functional properties than their parent protein molecules and consequently exhibit higher activity in food systems (Kamnerdpetch, Weiss, Kasper, & Scheper, 2007; Moreno et al, 1993). Moreover, potato protein hydrolysates have also been shown to have beneficial health effects in vivo (Chuang et al, 2020), illustrating their potential as both a functional and bioactive ingredients.…”
Section: Introductionmentioning
confidence: 99%